2014
DOI: 10.1117/12.2037058
|View full text |Cite
|
Sign up to set email alerts
|

Polymeric waveguide Fabry Perot resonators

Abstract: Optical microcavities are used in variety of applications ranging from sensors to lasers and signal routing in high volume communication networks. Achieving a high quality factor (Q) is necessary for achieving the higher sensitivity in sensing applications and for narrow linewidth light emission in most lasing applications. In this work, we propose a new way for achieving a higher quality factor in thin film, Fabry-Perot polymeric optical resonators. We show that lateral photon confinement in a vertical Fabry-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…In 1973, Thomson et al (53) firstly demonstrated an FP resonator to detect acoustic surface vibration. This kind of sensor has been gradually developed in terms of physical structure (54,55), compositive materials (56)(57)(58)(59) and new technologies (60)(61)(62)(63). FP sensors with excellent performances are suitable for photoacoustic endoscopy in medical applications (61,64).…”
Section: Fp Resonatorsmentioning
confidence: 99%
“…In 1973, Thomson et al (53) firstly demonstrated an FP resonator to detect acoustic surface vibration. This kind of sensor has been gradually developed in terms of physical structure (54,55), compositive materials (56)(57)(58)(59) and new technologies (60)(61)(62)(63). FP sensors with excellent performances are suitable for photoacoustic endoscopy in medical applications (61,64).…”
Section: Fp Resonatorsmentioning
confidence: 99%